Effect of beam current on defect formation by high-temperature implantation of Mg ions into GaN. (20th January 2022) - Itoh, Yuta; Watanabe, Hirotaka; Ando, Yuto; Kano, Emi; Deki, Manato; Nitta, Shugo; Honda, Yoshio; Tanaka, Atsushi; Ikarashi, Nobuyuki; Amano, Hiroshi
Abstract: We evaluated the beam current dependence of defect formation during Mg ion implantation into GaN at a high temperature of 1100 °C with two beam currents. Photoluminescence spectra suggest that low-beam-current implantation reduced the vacancy concentration and activated Mg to a greater extent. Moreover, scanning transmission electron microscopy analysis showed that low-beam-current implantation reduced the density of Mg segregation defects with inactive Mg and increased the density of intrinsic dislocation loops, suggesting decreases in the densities of Ga and N vacancies. The formation of these defects depended on beam current, which is an important parameter for defect suppression.